Daya Prediksi Tugas Problem Solving Terhadap Penguasaan Konsep Matematika Prodi Teknik Sipil - Rianto, Anto (Faculty of Technological and Vocational Education-Universitas Pendidikan Indonesia, 2011)
Problem solving skills are something essential to achieve success in various activities in everyday life. To train students’ intellectual to have them problem solving skills, the students are given the opportunity to explain the answer with its own language. Beside that they should be given the opportunity to behave as an expert and should be given the emphasis on qualitative issues as well. One of forms in training problem solving skills is by problem solving tasks. The results of research showed that the level of student mastery of problem solving tasks is good category, while the average level of student mastery of math concepts is medium category. Large contribution from the mastery of problem solving tasks of mastering math concepts at 82.9%. This shows that the mastery of problem solving tasks can contribute to student mastery of math concepts. Based on the coefficient of determination can be stated that the level of mastery of problem solving tasks can be used as a reference in predicting students' mastery of math concepts.